Cognitive Profile of Children With Intracranial Germ Cell Tumor According to Tumor Location. Issue 7 (October 2018) - Coutinho, Virginie; Dellatolas, Georges; Castaignede-Lalande, Clemence; Longaud-Vales, Audrey; Kieffer, Virginie; Guerrini-Rousseau, Lea; Grill, Jacques; Valteau-Couanet, Dominique; Dufour, Christelle
Abstract : Purpose: The purpose of this study was to evaluate the long-term cognitive sequelae and to describe the neuropsychological profile of patients with intracranial germ cell tumors according to tumor location (pineal or suprasellar site). Patients and Methods: Forty-five children treated at Gustave Roussy between 1991 and 2010 were assessed with neuropsychological tests to measure IQ, memory, visuospatial, motor, and executive skills at a mean delay of 4.2 years after diagnosis. All patients have received chemotherapy associated with surgery in 17 cases. Thirty-nine patients received, radiotherapy (focal 27, focal plus ventricles 8, craniospinal 4). Twenty-three patients had 2 IQ assessments with a mean delay of 4.1 years between the first and second. Results: Full scale IQ was preserved, with higher verbal IQ than other IQ indexes. Visuospatial, fine-motor, and executive difficulties were present in a significant proportion of patients. Visuospatial and fine-motor deficits were significantly associated with oculomotor difficulties, more present in the pineal than in the suprasellar group. No cognitive decline was observed between the first and the second IQ assessment. Conclusions: Overall cognitive abilities were preserved in children treated for central nervous system germ cell tumor.